Validity of a Sham Dry Needling Technique on a Healthy Population - Daniel M Cushman; Anna Holman; Lee Skinner; Keith Cummings; Peter Haight; Masaru Teramoto (North American Sports Medicine Institute, 2021)
# Background Various methods of sham procedures have been used in controlled trials evaluating dry needling efficacy although few have performed validation studies of the sham procedure. # Hypothesis/Purpose The purpose of this study was to examine the validity of a sham dry needling technique on healthy, active subjects. # Study Design Validation study # Methods Runners capable of completing a half-marathon or marathon race and were randomized to receive true (using an introducer and needle) or sham (using an introducer and fixed, blunted needle) dry needling. Blinded subjects were asked to identify if they received sham or true dry needling following the procedure. Proportions of those who correctly identified their needling were also examined on the basis of past experience of receiving dry needling. # Results Fifty-three participants were included in this study, with 25 receiving the true dry needling procedure and 28 receiving the sham. Of those who had received dry needling in the past (n = 16), 11 (68.8%) correctly identified their respective groups. For those who had not previously received dry needling (n = 37), 13 (35.1%) accurately identified their group. Most importantly, 94.1% of dry needling-naïve participants were unable to identify they received the sham procedure (p < 0.001). # Conclusions This study shows that a fixed needle in an introducer tube is a simple, inexpensive, effective sham procedure in patients who have never received dry needling before. This technique may be useful for randomized controlled trials in the future. # Levels of Evidence 2